Analysis of Depreciation of Fixed Assets and Their Use on the Performance of Medan City Government BKD Employees - Bella Nurhudiani; Rahmat Daim Harahap (Jurnal Mutiara Ilmu Akuntansi, 2023)
This research was conducted to analyze how depreciation of fixed assets and their use affects the performance of Medan City BKD employees. Fixed assets are a very important thing in a company, especially Medan City government offices, because without assets, employee performance will not run well and will of course cause various operational activities in the Medan City BKD to be hampered. The data collection technique in this research uses documentation studies such as studying documents related to problems or data such as fixed asset reports at the end of 2021 which are sourced directly from the Medan City BKD. This research uses qualitative methods with a field research strategy. The research results explain that asset managers do not record depreciation of fixed assets. Therefore, the researcher analyzed and calculated depreciation using the straight line method manually in the fixed asset management report which was stated to be good, only that the facilities and infrastructure or equipment such as computers were not sufficient for the number of employees based on research results which showed that maintenance of fraudulent assets was optimal so that there were some are idle and unused computers.